PENGARUH MODEL COOPERATIVE LEARNING TIPE GIVING QUESTION AND GETTING ANSWER TERHADAP PENINGKATAN KETERAMPILAN KOMUNIKASI SISWA PADA PEMBELAJARAN IPS DI SD - Puput Trisnawati; Eka Putri, Hafiziani; Caturiasari, Jennyta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Communication skills are an important component in social studies learning in elementary schools. However, the reality shows that students' communication skills are still relatively low. One of the factors suspected to be the cause is the inappropriate selection of learning models to support the improvement of students' communication skills. The purpose of this study was to examine the effect of the Giving Question and Getting Answer type of cooperative learning model on improving students' communication skills in social studies learning in elementary schools. The study was conducted with a quantitative approach using a quasi-experimental design with a non-equivalent control group type. The research sample consisted of two classes, namely IVC and IVB, in one of the elementary schools in Purwakarta Regency, totaling 25 students in each class. The IVC class acts as an experimental group using the Giving Question and Getting Answer cooperative learning model, while IVB as a control group uses the Jigsaw cooperative model. Data collection techniques are carried out through tests (pre-test and post-test) and non-test techniques (observation). The results of data analysis show a significant influence of the Giving Question and Getting Answer cooperative model on improving elementary school students' communication skills compared to the Jigsaw model. Based on the results of the study, it is recommended that this model be used as an alternative in social studies learning to create an interactive, participatory learning atmosphere and support the improvement of students' communication skills.